Loss of Angiotensin-Converting Enzyme-2 Exacerbates Diabetic Cardiovascular Complications and Leads to Systolic and Vascular Dysfunction A Critical Role of the Angiotensin II/AT1 Receptor Axis - Patel, Vaibhav B. (2012)
RATIONALE: Diabetic cardiovascular complications are reaching epidemic proportions. Angiotensin-converting enzyme-2 (ACE2) is a negative regulator of the renin-angiotensin system. We hypothesize that loss of ACE2 exacerbates cardiovascular complications induced by diabetes. OBJECTIVE: To define the role of ACE2 in diabetic cardiovascular complications. METHODS AND RESULTS: We used the well-validated Akita mice, a model of human diabetes, and generated double-mutant mice using the ACE2 knockout (KO) mice (Akita/ACE2(−/y)). Diabetic state was associated with increased ACE2 in Akita mice, whereas additional loss of ACE2 in these mice leads to increased plasma and tissue angiotensin II levels, resulting in systolic dysfunction on a background of impaired diastolic function. Downregulation of SERCA2 and lipotoxicity were equivalent in Akita and Akita/ACE2KO hearts and are likely mediators of the diastolic dysfunction. However, greater activation of protein kinase C and loss of Akt and endothelial nitric oxide synthase phosphorylation occurred in the Akita/ACE2KO hearts. Systolic dysfunction in Akita/ACE2KO mice was linked to enhanced activation of NADPH oxidase and metalloproteinases, resulting in greater oxidative stress and degradation of the extracellular matrix. Impaired flow-mediated dilation in vivo correlated with increased vascular oxidative stress in Akita/ACE2KO mice. Treatment with the AT1 receptor blocker, irbesartan rescued the systolic dysfunction, normalized altered signaling pathways, flow-mediated dilation, and the increased oxidative stress in the cardiovascular system. CONCLUSIONS: Loss of ACE2 disrupts the balance of the renin-angiotensin system in a diabetic state and leads to an angiotensin II/AT1 receptor-dependent systolic dysfunction and impaired vascular function. Our study demonstrates that ACE2 serves as a protective mechanism against diabetes-induced cardiovascular complications.